Oral health among children attending an oncology clinic in Trinidad - Anne Kowlessar; Rahul Naidu; Visha Ramroop; Janelle Nurse; Kavita Dookie; Curt Bodkyn; Sanjay Lalchandani (Wiley, 2019)
Abstract Objectives Little is known about the oral health of paediatric oncology patients in the Caribbean. Poor oral health can complicate oncology treatment, negatively affecting a child's health. In children undergoing chemotherapy or bone marrow transplant, odontogenic infections can progress to life‐threatening sepsis. The aim of this study is to investigate the oral health among children attending an oncology clinic in Trinidad. Material and Methods Sample population included paediatric oncology patients attending a children's hospital in Trinidad. Subsequent to obtaining informed consent, a 14‐item questionnaire was administered to parents/caregivers. An intra‐oral examination was undertaken by two dentists to assess soft tissues, gingival health, and dentition status, using visual examination only. Results Seventy‐one children and their caregivers participated in the study. The children consisted of both patients warded or attending as outpatients; 53.5% of patients were male and the mean age 6.64 (SD 3.33) years with a range of 1 to 15 years. Gingivitis and mucositis were present among 41.3% and 3% of patients, respectively. The prevalence of visible dental caries was 54.3%. Caries experience (dmft) was 2.28 (SD 3.63), and for those children with some caries experience (dmft > 0), this was 5.59 (SD 3.72). The majority (62.5%) had never visited a dentist. The most common dental treatment needs were dental prophylaxis (98.4%) and restorative treatment (50.8%). Acute lymphocytic leukaemia (39.1%) was the most common malignancy among this sample, and patients were at varying stages of cancer treatment. Conclusions Oral health among this sample of paediatric oncology patients was generally poor, with untreated caries being common, and the majority of children not having had any previous dental care. Preventive dental care for these patients should include oral hygiene instruction, dietary advice, topical fluoride application along with management of carious lesions, and odontogenic infections. This preliminary study highlights the need for closer collaboration between general dental practitioners, paediatric dentists, and paediatric oncology physicians, in caring for these patients.